miR-214 Protects Against Uric Acid-Induced Endothelial Cell Apoptosis - Yang, Bingyu; Li, Shuzhen; Zhu, Jun; Huang, Songming; Zhang, Aihua; Jia, Zhanjun; Ding, Guixia; Zhang, Yue (Frontiers in Medicine, 2020)
Background: Uric acid (UA) has been reported to be an important risk factor for cardiovascular diseases and can cause endothelial cell apoptosis through unclear mechanisms. Accumulating evidence has demonstrated that miR-214 plays a pivotal role in the pathogenesis of cardiovascular diseases. This study was to investigate the role of miR-214 in UA-induced endothelial cell apoptosis and the underlying mechanism. Material and methods: We enrolled 30 patients with hyperuricemia and 32 healthy controls and analyzed the levels of miR-214 in the serum of the participants. Then mouse aorta endothelial cells (MAECs) were treated with UA to induce cell apoptosis. An miR-214 mimic and a specific COX-2 inhibitor (NS398) were used to confirm the roles of these molecules in mediating UA-induced MAEC apoptosis or COX-2/PGE2 cascade activation. Results: A significant reduction in circulating miR-214 in the hyperuricemia patients compared with the healthy controls, along with a negative correlation with UA levels was observed. In the MAECs, UA treatment strikingly increased apoptosis as shown by the upregulation of BAX and cleaved Caspase-3 and the increased number of apoptotic cells. Interestingly, the expression of COX-2 was also upregulated at both the protein and mRNA levels during UA-induced cell apoptosis. In addition, an miR-214 mimic blocked UA-induced MAEC apoptosis, COX-2 induction and PGE2 secretion. The inhibition of COX-2 markedly ameliorated UA-induced apoptotic response and PGE2 production in MAECs. Luciferase activity assays further confirmed that COX-2 is a target gene of miR-214 in endothelial cells. Conclusion: We concluded that miR-214 could alleviate UA-induced MAEC apoptosis possibly by inhibiting the COX-2/PGE2 cascade.